How Latinas’ views of campus climate and gender role expectations contribute to their persistence at a two-year Hispanic serving institution - Laird, Susan E. (Kansas State University, 2014)
This qualitative case study with multiple participants explored how the perception of campus climate and gender role expectations contributes to Latinas’ persistence at a two-year Hispanic Serving Institution (HSI) in the Midwest. Guided by the work of Hurtado and Carter (1997) and social support theory (Sarason & Sarason, 1985), various aspects of the college experience both inside and outside the classroom were examined. In-depth interviews were conducted in order to gain insight into those viewpoints that influenced the desire to enroll and persist in college and how these perspectives shaped commitment and sense of belonging to the institution. Prominent themes that emerged were: the significance of family support and the need to stay close, the impact of student identity and the importance of positive faculty-student interaction. The results indicated that immigration status, the desire to make family proud, and support from family and instructors that offered words of encouragement served to motivate students to persist and graduate. Additional prominent findings revealed that the perception regarding academic environment including the need for positive academic advising experiences, involvement in organizational memberships, particularly with the Hispanic American Leadership Organization (HALO) and activities that embrace the diverse student population and incorporate varying perspectives affect perceptions of campus climate and commitment to the institution. Participants identified those programs and services on campus that best serve the needs of Latinas and have the most impact on a positive college experience. The results contribute to the research addressing campus climate and sense of belonging for Latino/a students overall, and offers unique insights from the perspective of Latinas attending a two-year HSI that is lacking in the body of literature. Implications for practice and future research are identified.
Keywords: Gender role expectations; Persistence; Latinas; Campus climate; Sense of belonging; Social support; Education, Community College (0275); Gender Studies (0733); Secondary Education (0533)